Comparison of premedication with or without vatinoxan, co-administered with medetomidine and methadone, in anesthetized dogs - Luca Bellini; Francesca Zanusso; Lorena Lucatello; Beatrice Dussin; Francesca Capolongo (Research in Veterinary Science, 2025)

A genetic algorithm-based approach for quantitative prediction of drug-drug interactions caused by cytochrome P450 3A inhibitors and inducers in dogs and cats - Veronica Di Paolo; Francesco Maria Ferrari; Italo Poggesi; Mauro Dacasto; Francesca Capolongo; Luigi Quintieri (Chemico-Biological Interactions, 2025)

Microplastics in inland and offshore sediments in the Apulo-Lucanian region (Southern Italy) - Vito Cofano; Daniela Mele; Maria Lacalamita; Paola Di Leo; Giovanni Scardino; Barbara Bravo; Francesca Cammarota; Domenico Capolongo (Marine Pollution Bulletin, 2023)

Fecal cortisol radioimmunoassay to monitor adrenal gland activity in the bottlenose dolphin ( Tursiops truncatus ) under human care - Barbara Biancani; Laura Da Dalt; Guglielmo Gallina; Francesca Capolongo; Gianfranco Gabai (Marine Mammal Science, 2017)
Fecal glucocorticoid measurement is an important noninvasive tool to monitor animal health. A radioimmunoassay ( RIA ) method was developed to measure fecal cortisol in bottlenose dolphins under human care. The method was used to measure baseline hormone levels and evaluate the adrenal response to environmental challenges in a small number of individual dolphins. The method was validated by precision and accuracy tests and by comparison with liquid chromatography‐mass spectrometry ( LC ‐ MS ). The parallelism test suggested few matrix interferences. The assay showed a good degree of precision within assay ( CV = 5.4%) and between assays ( CV = 4.1%). The RIA significantly correlated with the LC ‐ MS method ( r = 0.838, P RIA and LC ‐ MS suggested that the RIA slightly underestimates fecal cortisol concentrations, although the degree of accuracy was good. This study established that bottlenose dolphins excrete appreciable amounts of fecal cortisol (healthy subjects: 0.2–9.5 ng/g). Therefore, chronic HPA axis activation may be monitored in fecal samples by immunoassays after validating a suitable extraction protocol. The RIA could discriminate conditions of stimulation (pregnancy, parturition, isolation, transportation) and inhibition (diazepam administration) of the HPA axis and may, therefore, be useful for monitoring dolphin well‐being.

A monitoring of chemical contaminants in waters used for field irrigation and livestock watering in the Veneto region (Italy), using bioassays as a screening tool - Marco De Liguoro; Mirco Dalla Bona; Guglielmo Gallina; Francesca Capolongo; Federica Gallocchio; Giovanni Binato; Vincenzo Di Leva (Environmental Science and Pollution Research, 2014)